Contribution by Anаtoly Nepokupnyi to the Commemoration of the Anniversary of the First Lithuanian Book - Šveikauskienė, Daiva (Lietuvių kalba, 2023)
We review events devoted to the anniversary of the first Lithuanian book which were held not only in Lithuania but in foreign countries as well. The publication “Catechism” (Katekizmas) by Martynas Mažvydas is briefly characterized in this article. We also detail the main events such as the speeches of famous politicians and personalities at the commemoration at the Lithuanian National Opera and Ballet Theatre and at the Parliament meeting, where Anatoly Nepokupnyi attended. A CD named “Year of the Lithuanian Book” (Lietuviškos knygos metai) and a miniature book one and a half centimetre in width and height were two of few publications prepared beside events. The play “Mažvydas” was staged in the theatre. One of the monuments is the peak on Tian-Shan mountains which was first reached by Lithuanian alpinists and named “Mažvydas”. We also briefly tell a story about how the original first Lithuanian book come from Odessa (Ukraine) into Lithuania just a few decades before the anniversary. We highlight events abroad by paying most of the attention to Slavic language nations. Probably, the biggest commemoration that happened in foreign countries was in Prague. There were 20 presentations in a conference which was being held for two days. During the conference eve, the new study was published reviewing Lithuanian literature from the times of “Catechism” to the present day. The festival organized by Europe Radio Broadcasters was held in Croatia where the Lithuanian radio participated after preparing the program based on Mažvydas “Catechism” hymns. Two conferences were held in Poland – one at Poznan University and one in Torun where one of two copies of the first Lithuanian book survived to this day is stored. The inclusion of the 450th anniversary of the first Lithuanian book to UNESCO anniversaries calendar helped a lot with getting public attention to Lithuanian press and making old writings relevant.